Percepções sobre dor crônica e o cuidado à saúde na atenção básica - Tanaka, Roberta Aoqui [UNIFESP] (2019)
In daily work in primary health care, the high demand of patients with complaints of chronic pain has provided questions on the resolution of care actions performed in primary health care. Thus, it is necessary to improve attention to the patient with chronic pain, seeking to ensure a more resolute and integral care in health education practices. This study aims to understand the perception of chronic pain, the self-care strategies of patients participating in a chronic pain group in a health service of São Bernardo do Campo/SP, and the understanding of the team responsible for the group about the health education process in this group. A cartography of an experience was performed in a group of chronic pain, in a health service, from the knowledge of the trajectories of the patients who participate in it, the look of the health professionals who perform it, and this researcher. Most patients have reported that the start of pain they feel is related to work. Pain is present in life, causing limitations in daily activities and work, dependence and support of family members. For some patients the pain is accepted as part of life and the suffering is evident. Patients reported benefits and improvement in pain after group activities, the benefits reflect in decreased medication use, and the importance of the interaction between them in the activities. The health professionals who care in the group describe it as a multidisciplinary teamwork, in which each one have a function in the activity. They promote in health education actions a change to a "healthier" lifestyle and there is a stimulus to self-care, with an opening to listen to the topics of interest to patients to then elaborate the activity that will be performed, considered as a space that reinforces the exchange of experiences. Patients report an improvement with group participation that is related to decreased pain, medication use, emotional well being, socialization and quality of life. The various contexts and life trajectories allowed to expose the experience of illness, making it possible to understand pain, its limiting aspects and strategies to care of pain, being a possibility of promoting care and an educational process with autonomy. Dialogic practices can represent advances for the clinic in primary health care, more comprehensive actions and more effective care.